Predictors of diastolic deceleration time of coronary flow velocity of infarct related and reference coronary artery assessed by transthoracic Doppler echocardiography in the chronic phase of successfully reperfused anterior myocardial infarction: relation to infarct size - Giga, Vojislav; Tesic, Milorad; Beleslin, Branko; Boskovic, Nikola; Sobic-Saranovic, Dragana; Jovanovic, Ivana; Nedeljkovic, Ivana; Paunovic, Ivana; Dedic, Srdjan; Djordjevic-Dikic, Ana (Frontiers in Cardiovascular Medicine, 2023)
Introduction High-frequency transthoracic Doppler echocardiography (TDE) enables the assessment of flow velocity and velocity pattern in different coronary arteries, including the assessment of diastolic deceleration time (DDT) of coronary flow velocity. Short DDT of infarct related artery (IRA) (<600 msec) in the acute phase of anterior myocardial infarction (MI) is the predictor of adverse left ventricular (LV) remodeling and prognosis. The significance of DDT of coronary flow velocity assessment in the chronic phase of anterior MI is not well established. Our study aimed to establish the predictors of DDT of the coronary flow velocity of infarct related (left anterior descendent-DDT of LAD) and reference coronary artery, evaluated by TDE, and to assess their relation to infarct size in the chronic phase of successfully reperfused first anterior MI. Methods Our study included 40 consecutive patients (34 men, mean age 52 ± 12 years) one month after the first anterior STEMI and single vessel disease successfully treated with primary PCI. All patients underwent SPECT MPI for the assessment of LV volumes, ejection fraction, and percentage of the myocardium with fixed perfusion abnormalities and echocardiographic examination including the evaluation of DDT of IRA and reference coronary artery TDE. Results DDT of LAD correlated significantly to the WMSI (r = −0.467, p = 0.002), LV end-systolic volume (r = −0.412, p = 0.008), LV ejection fraction (r = 0.427, p = 0.006), while the strongest correlation was observed between DDT of LAD and the extent of fixed perfusion abnormality (r = −0.627, p < 0.0001), Multivariate analysis revealed percentage of fixed perfusion abnormalities along with DDT of reference coronary artery as the independent predictors of DDT of IRA. DDT of IRA shorter than 886 msec predicts large fixed perfusion abnormalities (>20%) with a sensitivity of 89% and specificity of 62% (AUC 0.842). Conclusion DDT of LAD assessed by TDE in the chronic phase of successfully reperfused first anterior MI is a usefull variable for the assessment of microcirculatory function that exclusively reflects the extent of microvascular damage and relates to infarct size.